Atividades experimentais investigativas como contribuição ao desenvolvimento de modelos mentais de conceitos químicos - Gibin, Gustavo Bizarria (2013)
In this study, during the school year, the evolution of mental models from first grade high school students about different chemical concepts was investigated by the use of experimental inquiry activities. The research was conducted in two public schools in the region of São Carlos-SP, with the participation of 04 teachers and 444 students divided into 11 classrooms. The methodology for data collection was divided into two steps. First, students performed experimental inquiry activities and were assessed through written individual and group activities, being also interviewed and filmed. These activities and interviews were useful for monitoring their mental models. It should be pointed out that the activities were developed based on the Curriculum Proposed by the Secretariat of Education of the State of São Paulo and the following chemical concepts were included: proposal for experimental procedure, submicroscopic representation of reactants and products, evidence of chemical reactions, Lavoisier s Law, concepts of reactants and products, Proust s Law and stoichiometry. In the second step of data collection, a short course was performed on the Laboratory for Chemistry Teaching and Learning (LENAQ). In this course the methodology used was the same as in the first step. Regarding the student s performance in the first step, it was observed that one third of the subjects showed oscillation in their mental models, 27.8% showed evolution of performance, 24.5% presented regression and 13.5% showed a constant performance. Thus, it can be inferred that although in some moments students showed evidence of difficulties in the development of mental models, the inquiry approach contributed to the development of the different chemical concepts. It should be emphasized that it was observed an evolution of a significant number of students regarding the development of experimental procedures. Finally, in the short course, improvements were observed in the constant and evolution performances in comparison to the school year.